Corporate Governance in Poland: the Impact of Mass Privatization - Ryszard Rapacki (ZBW - Leibniz Information Centre for Economics; ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2000)
The aim of the present paper is to discuss the role of the Mass Privatization Programme (MPP) in Poland, as a vehicle of change in the prevailing patterns of corporate governance in the emerging market economy. It is claimed that the Programme (also known as the National Investment Funds, or NIF, scheme) deserves the name of a genuine institutional innovation, as a novel way of effective privatization of firms involved coupled with their overhaul and in-depth restructuring. Unlike similar mass privatization schemes in other transition economies (e.g. Russia, Czech Republic or Slovakia) the Polish NIF Programme has had institutional guarantees built in for effective enforcement of private-like ownership rights and market-compatible corporate governance patterns.
Conference: VI World Congress of the International Council for Central and East European Studies, Tampere, 29 July-3 August, 2000; Additional information: Paper prepared for the VI World Congress of the International Council for Central and East European Studies, Tampere, 29 July-3 August, 2000.
Keywords: P34; P35; 330; privatization; Poland; privatization; Poland